2022
DOI: 10.1186/s40168-022-01321-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial functional genes are driven by gradients in sediment stoichiometry, oxygen, and salinity across the Baltic benthic ecosystem

Abstract: Background Microorganisms in the seafloor use a wide range of metabolic processes, which are coupled to the presence of functional genes within their genomes. Aquatic environments are heterogenous and often characterized by natural physiochemical gradients that structure these microbial communities potentially changing the diversity of functional genes and its associated metabolic processes. In this study, we investigated spatial variability and how environmental variables structure the diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 82 publications
4
16
0
Order By: Relevance
“…Complementarily, previous results show that the Dead Zone bacteria tend to be more metabolically similar to each other when compared to bacteria from oxic sediments (Broman et al, 2022). Our observation confirms a recent study that observed microaerophilic microorganisms from diverse environments present smaller genome sizes than obligate anaerobic (Nielsen et al, 2021).…”
Section: Benthic Metagenomes and Mags Show Bigger Estimated Average G...supporting
confidence: 91%
See 3 more Smart Citations
“…Complementarily, previous results show that the Dead Zone bacteria tend to be more metabolically similar to each other when compared to bacteria from oxic sediments (Broman et al, 2022). Our observation confirms a recent study that observed microaerophilic microorganisms from diverse environments present smaller genome sizes than obligate anaerobic (Nielsen et al, 2021).…”
Section: Benthic Metagenomes and Mags Show Bigger Estimated Average G...supporting
confidence: 91%
“…The top 2 cm of sediment was collected at soft bottom clay-muddy habitats from 59 stations from north to south in the Baltic Sea in 2019, following the sampling described in Broman et al, (2022) ( Supplementary Table 1 for coordinates). Briefly, one sediment core was collected per station using a Kajak gravity corer (surface area: 50 cm 2 , one core per station) and the top 0–2 cm layer was sliced into a 215 ml polypropylene container (207.0215PP, Noax Lab, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies reported maricultural farms as a point-source ( Lin et al, 2015 ; Muziasari et al, 2016 ; Gao et al, 2018 ) and terrestrial runoffs as a primary non-point source ( Chen et al, 2013a , b ) leading to the enrichment of ARGs in coastal sediments. Terrestrial runoffs commonly lead to multiple environmental gradients from bay to offshore areas ( Hou et al, 2014 ; Wang et al, 2015 ; Zhang H. et al, 2018 ; Broman et al, 2022 ). However, our knowledge about geographic patterns of antibiotic resistomes in sediments across coastal ecological gradients is still lacking.…”
Section: Introductionmentioning
confidence: 99%